PELATIHAN MEDIA PEMBELAJARAN SECARA VIRTUAL DI MASA PANDEMI COVID-19 - Tamrin, A. F.; Parwoto, Parwoto (Buletin Udayana Mengabdi; Vol 20 No 4 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i04.p05, 2022)
Learning media is important in the learning process. However, in use it is often ignored by teachers for various reasons. This community service activity aims to provide assistance to train PAUD teachers in making interactive learning media. The community service participants are approximately 5 PAUD teachers. The method used is descriptive method. The mentoring activity was carried out five times by presenting the material then continued with training on making interactive learning media. The conclusion of the implementation carried out can provide new knowledge to teachers in using learning media and using technology in the learning process. The resulting learning media are in the form of videos and picture books that can attract students' attention to study independently.